We, the people of Europe? : reflections on transnational citizenship - Balibar, Étienne, 1942- (Translation/transnation., 2004)
Etienne Balibar has been one of Europe's most important philosophical and political thinkers since the 1960s. His work has been vastly influential on both sides of the Atlantic throughout the humanities and the social sciences. In We, the People of Europe?, he expands on themes raised in his previous works to offer a trenchant and eloquently written analysis of "transnational citizenship" from the perspective of contemporary Europe. Balibar moves deftly from state theory, national sovereignty, and debates on multiculturalism and European racism, toward imagining a more democratic and less stat.